2019
DOI: 10.1109/access.2019.2956770
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Literature Review on Penetration Testing for Mobile Cloud Computing Applications

Abstract: Mobile cloud computing (MCC) enables mobile devices to exploit seamless cloud services via offloading, and has numerous advantages and increased security and complexity. Penetration testing of mobile applications has become more complex and expensive due to several parameters, such as the platform, device heterogeneity, context event types, and offloading. Numerous studies have been published in the MCC domain, whereas few studies have addressed the common issues and challenges of MCC testing. However, current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…SLR process has some steps (Qasem et al, 2019;Salleh et al, 2018;Rosati et al, 2017;Hidayat, Azzery, & Mahardiko, 2019;Sharma & Singh, 2017;AlAhmad et al, 2019;Christo et al, 2019;Boomija, 2016;Shen & PenaMora, 2018). First, we had to define the problems.…”
Section: Methods 31 Systematic Literature Review (Slr) Processmentioning
confidence: 99%
“…SLR process has some steps (Qasem et al, 2019;Salleh et al, 2018;Rosati et al, 2017;Hidayat, Azzery, & Mahardiko, 2019;Sharma & Singh, 2017;AlAhmad et al, 2019;Christo et al, 2019;Boomija, 2016;Shen & PenaMora, 2018). First, we had to define the problems.…”
Section: Methods 31 Systematic Literature Review (Slr) Processmentioning
confidence: 99%
“…Secondary studies in mobile app testing have been predominant over the last two years [3,4,48,59,80,86]. Luo et al [59] aimed to give an overview of the simulation methods, i.e., data-driven and model-based, for testing mobile context-aware applications.…”
Section: Sotware Testing Toolsmentioning
confidence: 99%
“…Moreover, we can observe that the topic is quite new with approximately 13 years of contributions, whereby the 58.9%(33/56) of primary studies were published during the last four years, as shown in Table 7. The growing interest of the community matches the raising number of smartphones sold from 2007 3 . We can observe a growing trend of works published in journals, showing that the quality of the works has reached a suicient quality.…”
Section: Rq1 1 Studies Over Timementioning
confidence: 99%
“…20 of these studies conducted SLR method. The vast majority of these studies have focused on a specific subject of cloud computing and searched the literature, such as, structural equation modeling in cloud computing (Pisirir et al, 2019), supply chain integration (Novais et al, 2019), cloud computing adoption in developing countries (Mrhaouarh et al, 2018), cloud computing service composition (Jula et al, 2014), open source cloud simulation platforms and types (Lynn et al, 2016), applying semantic technologies in cloud computing (Brabra et al, 2016), resource scheduling and security in cloud computing (Sheikh et al, 2019), penetration testing in Mobile Cloud Computing apps (Al-Ahmad et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%